2012
DOI: 10.1007/s00128-012-0887-1
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Bisphenol A, Estrone, 17β-Estradiol and 17α-Ethinylestradiol in Portuguese Rivers

Abstract: O PDF relativo ao artigo que solicita, não se encontra disponível em Acesso Aberto. Motivos: O editor não permite o depósito e disponibilização em acesso aberto do PDF que solicita. Para consultar o documento deve aceder ao endereço do editor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 13 publications
0
20
0
1
Order By: Relevance
“…More than 100 t of the annual BPA production volume is released into the atmosphere (Vandenberg et al 2009 ;Cao et al 2011 ). This volume of release has made BPA environmentally ubiquitous; BPA residues are found in air, drinking water, lakes, the seas, sewage sludge, soil, house dust, foodstuffs, paper currency, among other objects and media (Ignatius et al 2010 ;Liao and Kannan 2011 ;Geens et al 2012 ;Hammer et al 2012 ;Liao et al 2012 ;Molina-García et al 2012 ;Rudel et al 2011 ;Wang et al 2012b ;Rocha et al 2013 ).…”
Section: Sources and Routes Of Bisphenol A Exposurementioning
confidence: 98%
“…More than 100 t of the annual BPA production volume is released into the atmosphere (Vandenberg et al 2009 ;Cao et al 2011 ). This volume of release has made BPA environmentally ubiquitous; BPA residues are found in air, drinking water, lakes, the seas, sewage sludge, soil, house dust, foodstuffs, paper currency, among other objects and media (Ignatius et al 2010 ;Liao and Kannan 2011 ;Geens et al 2012 ;Hammer et al 2012 ;Liao et al 2012 ;Molina-García et al 2012 ;Rudel et al 2011 ;Wang et al 2012b ;Rocha et al 2013 ).…”
Section: Sources and Routes Of Bisphenol A Exposurementioning
confidence: 98%
“…The selected concentration of EE 2 is environmentally relevant, as in surface waters the majority of the detected EE 2 concentrations range from non-detectable to 5 ng/L (Belfroid et al, 1999;Cargouet et al, 2004;Rocha et al, 2012Rocha et al, , 2013. The Fad concentration used (50 g/L) was selected based on previous studies conducted in zebrafish (Andersen et al, 2004) and other fish species (Ankley et al, 2002;Zhang et al, 2008), where masculinization induction was reported.…”
Section: Exposure Conditionsmentioning
confidence: 99%
“…Three exposure conditions were set up, in duplicate: an experimental control, EE 2 (4 ng/L) and Fad (50 g/L). The selected concentration of EE 2 is environmentally relevant, as in surface waters the majority of the detected EE 2 concentrations range from non-detectable to 5 ng/L (Belfroid et al, 1999;Cargouet et al, 2004;Rocha et al, 2012Rocha et al, , 2013. The Fad concentration used (50 g/L) was selected based on previous studies conducted on zebrafish (Andersen et al, 2005;Luzio et al, 2015bLuzio et al, , 2016a and other fish species (Ankley et al, 2002;Zhang et al, 2008), where induction of masculinization was reported.…”
Section: Experimental Designmentioning
confidence: 99%